Making Space for Myth: Worldbuilding and Interconnected Narratives in Mythspace - Quina, Francis Paolo (SARE: Southeast Asian Review of English, 2021)
The comics medium has long proven to be fertile ground for worldbuilding, spawning not only imaginary worlds but multiverses that have become international transmedial franchises. In the Philippines, komiks (as it is called locally) has provided the Filipino popular imagination with worlds populated by superheroes, super spies, supernatural detectives, and creatures from different Philippine mythologies. The komiks series Mythspace, written by Paolo Chikiamco and illustrated by several artist-collaborators, takes the latter concept, and launches it into outer space. Classified by its own writer as a “Filipino space opera” consisting of six loosely interconnected stories, Mythspace presents a storyworld where the creatures of Philippine lower mythologies are based on various alien species that visited the Philippines long ago. The article will examine the use of interconnected narratives as a strategy for worldbuilding in Mythspace. Drawing from both subcreation and comic studies, this article posits that interconnected narratives is a worldbuilding technique particularly well-suited to comics, and that the collaborative nature of the medium allows for a diversity of genres and visual styles that can be used by future komiks creators to develop more expansive storyworlds.